TEACHING CULTURE IN EFL CLASSES (Konferensiyalar | Conferences, 2024)
Language learning and teaching have long been the subject of academic research and practical application. However, the role of culture in this process has often been overlooked. Culture is an essential element in language learning and teaching, as it shapes the way in which language is used and understood. This paper argues that cultural awareness and sensitivity are crucial for effective language learning and teaching. It addresses the importance of building bridges between different cultures through language learning, and suggests that teaching language and culture together can lead to greater success in both areas. It also learning how learning culture of the target can language can help uses to avoid miscommunications and conflicts and proposes some ways to implement teachers to teach culture. The paper concludes by asserting that a multicultural approach to language learning and teaching can enrich the learning experience and better prepare students for a globalized world.